From law enforcement to public safety: Police officer experiences of naloxone administration to reverse opioid overdose in New York City - Bennett Allen; Alex Harocopos (PLoS ONE, 2026)
The overdose epidemic has reshaped law enforcement’s relationship with public health, as police increasingly adopt overdose response measures, including naloxone training and use. This study analyzed 15 interviews with New York Police Department (NYPD) officers to examine their experiences administering naloxone in their duties. Naloxone was seen as facilitating a shift from traditional law enforcement to a broader public safety role, and officers noted its potential to improve public perceptions of police. However, tensions emerged as officers navigated dual roles in enforcement and health, with concerns that overdose reversal might enable continued drug use or crime. Additionally, officers expressed frustrations about naloxone’s limitations, particularly its inability to address systemic barriers to addiction recovery. These findings underscore the need for clear policies, comprehensive training, and stronger interagency partnerships to enhance the integration of public health strategies within policing and better support officers in responding to the overdose crisis.